Arabian toadfish Colletteichthys occidentalis Greenfield, 2012 from Northern Arabian Gulf off Iraq - Al-Faisal, Abbas T.; Mutlak, Falah M. (Mesopotamian Journal of Marine Sciences, 2025)
The Confirmation of the presence of Arabian toadfish Colletteichthys occidentalis Greenfield, 2012 , is reported from northern Arabian Gulf off Iraq. The sample was collected using a trawl net in May 2024. C. occidentalis is characterized by a single tentacle located above the posterior portion of the eye, dorsal fin rays 19, anal fin rays 15.